(untitled) (Research, Society and Development, 2025)
Introduction: The Placenta Accreta Spectrum is characterized by the abnormal invasion of placental tissue into the myometrium, associated with a high maternal risk. Method: This analysis consists of a literature review based on articles selected from the PubMed and SciELO databases, published in the last 15 years. Results and Discussion: The Placenta Accreta Spectrum is characterized by the abnormal invasion of placental villi into the myometrium, associated with a high risk of maternal morbidity and mortality, especially in pregnant women with previous cesarean sections and placenta previa. Early diagnosis, preferably by ultrasound with Doppler in the second trimester, is essential for obstetric planning and can be supplemented by magnetic resonance imaging between 28 and 34 weeks in doubtful cases. The ideal management includes elective cesarean delivery for between 34 and 36 weeks in specialized centers, with a multidisciplinary team, frequent use of cesarean hysterectomy without placental detachment, and, in selected cases, a conservative approach. International guidelines emphasize the importance of systematic screening, early referral, and informed consent to optimize maternal and neonatal outcomes. Conclusion: Referral to specialized centers, planning for elective delivery, and antepartum diagnosis with referral to specialized centers and planning for elective delivery are essential to minimize hemorrhagic risks. The integration of imaging diagnosis, clinical assessment, and a multidisciplinary team is crucial to improve maternal and neonatal outcomes, preventing severe complications.